2018
DOI: 10.11646/zootaxa.4496.1.34
|View full text |Cite
|
Sign up to set email alerts
|

New species and records of earthworms (Annelida, Oligochaeta) in plantain cropping systems in Colombia's coffee-growing region

Abstract: Two new earthworm species, one of Glossodrilus Cognetti, 1905 and the other of Martiodrilus (Maipure) Righi, 1995, are described from material collected from the coffee-growing region located in central-western Colombia: Glossodrilus chaguala sp. nov., and Martiodrilus (Maipure) quimbayaensis sp. nov. New records for this region are also reported for Glossodrilus griseus, Glossodrilus lacteus, Glossodrilus panikita, Aptodrilus fuhrmanni, Periscolex columbianus, Periscolex coreguaje, Pontoscolex (Pontoscolex) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 1,158 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In Asia, 35 species were recorded, with a higher proportion of natives (66%). In North and South America, around 50% of the species found were native, but these were mainly due to the higher number of natives observed in Colombian (Feijoo et al 2018) and Mexican (Geissen et al 2009;Huerta et al 2013) plantations.…”
Section: Earthworm Communities In Banana Plantations Worldwidementioning
confidence: 98%
See 2 more Smart Citations
“…In Asia, 35 species were recorded, with a higher proportion of natives (66%). In North and South America, around 50% of the species found were native, but these were mainly due to the higher number of natives observed in Colombian (Feijoo et al 2018) and Mexican (Geissen et al 2009;Huerta et al 2013) plantations.…”
Section: Earthworm Communities In Banana Plantations Worldwidementioning
confidence: 98%
“…Interestingly, two of the major banana-producing countries in terms of area were not represented (Tanzania, Rwanda), and in China (another important producer), only one study reported earthworms from a single site (Sun et al 2012). Plantain banana fields were sampled in only 22 locations (10% of total) in four countries (Colombia, Cameroon, Ivory Coast and Ecuador;Tondoh 2007;Norgrove et al 2011;Avilés 2017;Feijoo et al 2018), and involved traditional management practices, rather than conventional cultivation. Most of the fields evaluated were banana plantations, and only in Ecuador were mixed banana/plantain fields evaluated (Avilés 2017).…”
Section: Earthworm Communities In Banana Plantations Worldwidementioning
confidence: 99%
See 1 more Smart Citation